Dietary lycopene and cardiovascular health in ethnic Lithuanians - Mažeikienė, Asta; Jakaitienė, Audronė; Karčiauskaitė, Dovilė; Kučinskienė, Zita Aušrelė; Abaravičius, Jonas Algis; Kaminskas, Arvydas; Kučinskas, Vaidutis (Acta medica Lituanica, 2016)
Background. Lycopene is a potent antioxidant, and it has been suggested that intake of lycopene-rich food results in a  decreased risk of cardiovascular diseases. However, no official recommendation of lycopene consumption from natural dietary sources exists, and intake data of the Lithuanian population are limited. The goal of this study was to evaluate the median intake of lycopene in ethnic Lithuanians and to relate lycopene intake with biochemical blood risk factors for CVD in the general population and different ethnolinguistic groups. Materials and methods. One thousand one hundred forty randomly selected individuals (2–85  years of age) from six Lithuanian ethnolinguistic regions provided 3-day diet records for evaluation of lycopene consumption. Individuals were interviewed using a validated questionnaire consisting of lifestyle and clinical data. Serum concentrations of total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglyceride, high-sensitivity C-reactive protein, glucose, apolipoprotein A-I, apolipoprotein B, lipoprotein (a) were measured using standardised procedures. Due to the non-normal distribution of variables, nonparametric tests were applied using the IBM SPSS v20.0 software. Results. The  mean dietary lycopene intake in the  study population was 5.05 ± 7.48 or 0.07 ± 0.11 mg/kg body weight per day. Major food sources of lycopene were tomatoes and tomato products (79%). The lycopene intake from natural dietary sources varied significantly between the  Lithuanian ethnolinguistic groups (the lowest intake 3.52 ± 5.64 mg/day, the highest intake 6.22 ± 7.66 mg/ day, p = 0.01) and genders (women 5.26 ± 7.78 mg/day and men 4.8 ± 7.22 mg/ day, p  =  0.01). The  mean lycopene intake was significantly (p
Keywords: lycopene; lycopene intake; antioxidants; cardiovascular diseases